Subjektivitas Anak Usia Dini Atas Kehilangan Ayah: Fenomenologi Kepercayaan Diri dan Karakter Profetik - Hidayat, Arif; Selina, Ristiana; Kuswanto , Kuswanto (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Fathers are not only biological parents, but also play an important role in shaping the self-confidence and identity of young children. The absence of a father, whether physical or emotional, can cause emotional trauma and hinder a child's psychological development from an early age. This study employs a phenomenological method with an Interpretative Phenomenological Analysis (IPA) approach to explore the meaning of the experiences of five young children at TK Taruna Bakti Bandung who grew up without a complete father figure. The findings reveal that the absence of a father significantly impacts the formation of a child's psychological structure and identity, weakening prophetic values such as love, responsibility, justice, and exemplary behavior. This condition also affects spiritual autonomy, social skills, and self-understanding. Patriarchal parenting patterns that marginalize the father's role as a moral-spiritual partner exacerbate the child's developmental conditions. Based on these findings, this study recommends the development of an early childhood education curriculum that is responsive to the needs of children from fatherless families through the integration of prophetic values, the strengthening of emotional literacy, and the cultivation of social skills. Additionally, school-based psychosocial interventions such as small group mentoring, counseling, and the involvement of surrogate father figures are needed to help children build a complete, resilient identity rooted in moral-spiritual values, even without the direct presence of a father.